Assessment of airflow limitation, airway inflammation, and symptoms during virus-induced wheezing episodes in 4- to 6-year-old children - Konstantinou, G. N.; Xepapadaki, P.; Manousakis, E.; Makrinioti, H.; Kouloufakou-Gratsia, K.; Saxoni-Papageorgiou, P.; Papadopoulos, N. G. (J Allergy Clin Immunol, 2013)
It is disputed whether recurrent episodes of wheeze in preschool-aged children comprise a distinct asthma phenotype.|We sought to prospectively assess airflow limitation and airway inflammation in children 4 to 6 years old with episodic virus-induced wheeze.|Ninety-three children 4 to 6 years old with a history of mild, virus-induced episodes of wheeze who were able to perform acceptable fraction of exhaled nitric oxide (Feno) maneuvers and spirometry (with forced expiratory time ≥0.5 seconds) were followed prospectively. Lung function and Feno values were measured every 6 weeks (baseline) within the first 48 hours of an acute wheezing episode (day 0) and 10 and 30 days later. Symptom scores and peak flow measurement were recorded daily.|Forty-three children experienced a wheezing episode. At day 0, Feno values were significantly increased, whereas forced expiratory volume at 0.5 seconds (FEV(0.5)) significantly decreased compared with baseline (16 ppb [interquartile range IQR, 13-20 ppb] vs 9 ppb IQR, 7-11 ppb] and 0.84 L [IQR, 0.75-0.99 L] vs 0.99 L [IQR, 0.9-1.07 L], respectively; both P < .001). Airflow limitation at day 0 was reversible after bronchodilation. FEV(0.5) and Feno values were significantly associated with each other and with lower and upper respiratory tract symptoms when assessed longitudinally but not cross-sectionally at all time points independently of atopy. Feno and FEV(0.5) values returned to baseline levels within 10 days.|Mild episodes of wheeze in preschoolers are characterized by enhanced airway inflammation, reversible airflow limitation, and asthma-related symptoms. Feno values increase significantly during the first 48 hours and return to personal baseline within 10 days from the initiation of the episode. Longitudinal follow-up suggests that symptoms, inflammation, and lung function correlate well in this phenotype of asthma.
Keywords: Child Child; Preschool Exhalation Female Forced Expiratory Volume Humans Inflammation Longitudinal Studies Male Reproductive Tract Infections Respiratory Sounds Spirometry